A study on factors other than monetary that influence job satisfaction in Shapadu Energy & Engineering Sdn Bhd, Shah Alam / Nurdini Zahari - Zahari, Nurdini (Faculty of Business and Management, 2010)
This research was conducted to determine the factors that can contribute to the employee satisfaction in their workplace. The main objective of this research is to study on the factors other than monetary that could motivate an employee. We aim to look at other qualities that employees depend on to assure their “staying power” at a particular employment. At the same time, the study was conducted to identify the major factors that contribute to the job performance in a high and deficient way. The study was conducted at Shapadu Energy and Engineering Sdn Bhd towards non-executive and executive employee level. The research was a quantitative research and the data used for the study was collected using the communication approach through distribution of questionnaires.